Blended Learning Modality in Teaching Statistics in a Graduate Program of a State University in the Philippines - Malonisio, Manuel Ortiz (SCAD Independent, 2023)
Graduate students commonly experience apprehension towards statistics courses, leading to lower achievement and negative perceptions of the subject. This mixed-methods research study aimed to explore the effects of blended learning on graduate students' achievement and perception of statistics in the Master of Arts in Education program. Blended learning combines online and face-to-face learning modalities. The study included 67 participants who completed tests for parametric and non-parametric statistics and 12 who underwent interviews. Results showed that students showed mastery of specific statistical topics, particularly correlation and regression tests and tests of difference with paired and independent samples. The students attributed their success to blended learning, which promotes flexibility, ease of learning statistics, independent learning, and motivation. Regardless of the field of specialization, students' scores in statistics were similar. However, challenges such as internet connection, software use, and technicalities of concepts and software like SPSS were reported. This study suggests that blended learning is beneficial for improving graduate students' achievement and perception of statistics and that proper support and guidance are needed to address the challenges of this learning modality.